ANALYSIS OF NETIZENS' INTERACTIONS ON GOVERNOR SHERLY TJOANDA'S TIKTOK ACCOUNT IN REFLECTING PUBLIC TRUST - Elda Lestari Setiawati; Raden Imam Al Hafis (Yayasan Wayan Marwan Pulungan, 2026)
Development of digital technology has changed the way of government communicates with public, especially through social media platforms. TikTok has become one of the media widely used by public officials to convey information, build closeness, and engage in direct interaction with the community. This study aims to analyze netizens' interactions on Governor Sherly Tjoanda's TikTok account in reflecting public trust in local government communication. This study uses a qualitative approach with content analysis methods in responses from netizens on comments section post from Governor Sherly Tjoanda's TikTok account. The observation period was set for 31 days in May 2026 because it is the latest period available at the time the study was conducted, so the data produced can represent the most current condition. Results of research indicate that public trust is reflected through various forms of interaction, such as support for government programs, appreciation of the governor's performance, positive responses to public service information, as well as active participation in discussions. These findings suggest that TikTok not only functions as a medium for information dissemination but also as a digital communication space that allows the public to express their views and level of trust in local government. Therefore, the use of interactive and responsive social media can be one of the supporting factors in strengthening the relationship between the government and the public in the digital era.